Subband HDTV coding using high-order conditional statistics - Lei, S.-M.; Chen, T.-C.; Tzou, K.-H. (IEEE journal on selected areas in communications, 1993)
An HDTV coding scheme that is capable of achieving high quality below 20 Mb/s is presented. The system employs motion estimation/compensation followed by four-band subband splitting. The band signals are then subject to quantization and coded by an innovative high-order entropy coder. It is shown that this high-order entropy coder generates a bit rate nearly 30% lower than that of run-length/Huffman coding for motion-compensated frame differences. About 15% improvement is observed for the intrafield coded data. To reduce the complexity of the high-order entropy coder for high-speed implementation, two techniques, codebook reduction and nonuniform quantization of conditioning samples, are developed. A method for selecting conditioning samples and their order, based on mutual information between samples, is proposed and shown to outperform several other systematic and intuitive approaches. Simulations show that the new system, at about 20 Mb/s, achieves picture quality comparable to that of a 120-Mb/s six-band intrafield coding system previously investigated.< >